Modeling snowflake divertors in MAST-U Tokamak. (2nd December 2021) - Khrabry, A.I.; Soukhanovskii, V.A.; Rognlien, T.D.; Umansky, M.V.; Moulton, D.; Harrison, J.R.
Abstract: In a snowflake (SF) divertor, two magnetic field nulls are placed close to each other, creating four strike points (SPs) compared to two in a standard X -point divertor. In preparation for MAST-U experiments, magnetic configurations with the standard and SF divertors with various locations and separation distances of the nulls were modeled using the two-dimensional multi-fluid code UEDGE with a full plasma transport model featuring charge-state-resolved sputtered carbon impurities. The complex interplay of the plasma transport and magnetic configurations was comprehensively studied using a simple model for the theoretically predicted fast plasma mixing driven by the 'churning' mode instability in the two-null SF region. The modeling results show that (1) all SF-plus configurations and SF-minus configuration with closely located nulls produce the same plasma parameters and heat fluxes at the same SPs; (2) SF divertors approach the outer and inner SP detachment conditions at lower upstream density w.r.t. the standard divertor; (3) heat flux profiles at primary SPs are substantially broadened and peak values are reduced in SF configurations w.r.t. SN divertors; this broadening becomes more pronounced with the fast plasma mixing increase.